Reviews of new publications - Holmes, Derek A (KUKILA, 1989)
Silvius, M.J., A.P.J.M. Steeman, E.T. Berczy, E. Djuharaa & A.M. Taufik. 1987. The Indonesian Wetland Inventory. A preliminary compilation of existing information on wetlands of Indonesia. P.M.P.A., A.W.B./Interwader, EDWIN: Bogor, Indonesia. Van Marle, J.G. & K.H. Voous. 1988. The birds of Sumatra.British Ornithologists Union Checklist no. 10. London. Collar N.J. & P. Andrew 1988. Birds to watch : The ICBP World Checklist of threatened birds. International Council for Bi rd Preservation Technical Publication no. 8. Amadon, 0. & J. Bull. 1988. Hawks and Owls of the World: a distributional and taxonomic list (with the genus Otus by Marshall, J.T. A B.F. King). Proc. Western Foundation Vert. Zool. 3 (4): 294-357.